NUMERICAL ANALYSIS OF TENSILE MECHANICAL PROPERTY OF GLASS FIBER REINFORCED EPOXY (The International Journal of Engineering & Information Technology (IJEIT), 2023)
In this paper a study has been carried out to find the characteristic relation between experimental and numerical analysis of tensile properties of glass fiber reinforced epoxy composite materials, which are subjected last before to tensile test using the universal testing machine. The numerical results obtained by finite element analysis were compared with available experimental data in literature for the tensile strength. The comparison shows that the results of tensile strength are in agreement with available experimental data published in literature. It was confirmed and enhancing validity of tensile properties of experimentally tested composite materials